2019
DOI: 10.3892/mmr.2019.10560
|View full text |Cite
|
Sign up to set email alerts
|

Allium�hookeri root extract regulates asthmatic changes through immunological modulation of Th1/Th2‑related factors in an ovalbumin‑induced asthma mouse model

Abstract: In 2013, WHO estimated that approximately 235 million people suffered from asthma worldwide. Asthma is a hyper responsive disorder, which is related to an imbalance between the T-helper type 1 and 2 cells (henceforth, Th1 and Th2, respectively). Allium hookeri is a plant that is widely used for culinary purposes and also in traditional Asian medicine. The present study was conducted to elucidate the anti-asthmatic effects and mechanism of action of A. hookeri root extracts (AHRE) in an ovalbumin (OVA)-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…And plenty of literature has shown that T lymphocyte retains influence on asthma. The mainstream view is that the pathogenesis of asthma is the imbalance of T cells differentiation (predominantly Th1/Th2), and various pro-inflammatory factors may greatly assist in Th2 inflammation [4].…”
Section: Open Accessmentioning
confidence: 99%
“…And plenty of literature has shown that T lymphocyte retains influence on asthma. The mainstream view is that the pathogenesis of asthma is the imbalance of T cells differentiation (predominantly Th1/Th2), and various pro-inflammatory factors may greatly assist in Th2 inflammation [4].…”
Section: Open Accessmentioning
confidence: 99%
“…Anti-IgE agents, such as omalizumab, are immunomodulatory and are called the 'magic bullet' for allergic asthma treatment as they can suppress the exacerbation of asthma [39]. In our lab, we have been concentrating on finding Th2 cell-suppressing agents from natural products [13,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Allium cepa L., which has long been used as an anti-inflammatory drug, downregulates Blomia tropicalis-induced Th2 cell-related cytokines, such as IL-4 and IL-13 [83]. Allium hookeri, which is used as a culinary material, significantly inhibits the release of Th2 cell-related cytokines, such as IL-4, IL-5, and IL-13 [84]. Anoectochilus formosanus HAYATA, a traditional drug, suppressed IgE, IL-4, and IL-5 levels in an asthma model [85].…”
Section: Immune Modulatorsmentioning
confidence: 99%